SCABIOSIS IN DOMESTIC CATS - Mahaputra, I Made; Widyastuti, Sri Kayati; Anthara, Made Suma (Buletin Veteriner Udayana, 2023)
Scabies is a skin disease that dominates both domesticated and wild cats caused by the zoonotic mite Sarcoptes scabiei . The purpose of writing this article is to provide information about the impact of scabies infection in cats and the appropriate treatment and handling given to cats with scabies cases. Examination was carried out on domestic cats with anamnesis showing symptoms of itching by scratching the ears against the wall or ground and found lesions on the ears. The results of clinical examination showed hyperkeratosis and alopecia in the ear. Investigations using skin scraping or skin scraping under a microscope showed Sarcoptes scabiei mites, while hematological examination revealed that the cat had leukocytosis and hyperchromic normocytic anemia. Based on the history, clinical examination and supporting examination, the cat was diagnosed with scabiosis. The therapy given is in the form of causative, symptomatic, and supportive therapy. The causative therapy given was ivermectin with a dose of 0.2 ml/kg body weight with two doses at an interval of 14 days. Symptomatic therapy given is Chlorpheniramine maleate given at a dose of 2 mg/kg body weight, every 12 hours, for five days. Supportive therapy is given in the form of Vita-Gel 50 g given the size of three corn kernels (1-3 cm) 2-3 times a day for 10 days, and animals are bathed using sulfur soap twice a week. The therapy given to the Pisci cat showed good results where the cat showed changes from the beginning until after the treatment the pruritus and hyperkeratosis began to decrease and the hair started to grow. If the owner's cat has scabies, immediately separate it from their pets so that scabies does not spread to other animals.